The Impact of Sustainability Reporting on Financial Performance: A Study Case of Indonesian Industry Company - Ramadhani, Fadhila Puput; Sukoharsono, Eko Ganis (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The purpose of this research is to analyze the impact of sustainability report disclosure on the financial performance of Indonesian industrial companies. This research presented here utilizes a sample of 91 GRI-Standard sustainability reports from 20 industrial companies registered with the NSCR (National Center for Sustainability Reporting) in the years 2019 to 2022. The data used in this study is secondary data, and the sample is drawn from a list of companies that frequently provide sustainability reports with the help of multiple regression analysis to the test hypothesis. The findings of this study show that only aggregate disclosure of sustainability reports, disclosure of the economic dimension, and disclosure of the social dimension impacted the financial performance of industrial companies this indicates that if the company incurs costs related to these aspects, it will improve its image among stakeholders and potential investors. Disclosure of the environmental dimension has no impact on the financial performance of industrial companies because the items produced by the company affect the company itself and are not felt immediately by all stakeholders, the existence or absence of items specified in the disclosure of environmental performance does not affect the rise and fall of financial performance.